The Declaration of Pakistan Resolution: The Unprecedented Demand for a Separate Homeland (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The year 1940 dawned with no hopes of solution and ranits languid course of interviews, statements when it was roused by thepublication of the Lahore Resolution of the Muslim League in March, 1940 withits demands of Pakistan. The whole country was taken by surprise at the mostunusual demand of the Muslim League for a separate homeland for Muslims on thesoil of India.